PERGESERAN MAKNA DAN PEMANFAATAN RUANG PEKAPALAN KERATON YOGYAKARTA - , Sri Sunarti, Prof. Ir. Sudaryono, M.Eng,Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Along with complex conditions in the Region of Yogyakarta Palace Pekapalan predominantly residential street vendors, homeless people, rows of stalls covering Pekapalan Ward, it is not proper condition is on the front face of the palace. This study aimed to describe the figure Pekapalan found Pekapalan shift related functions as an integral part of the Palace Square north Ngayogyokarto Sultanate that has significant value once the image of Yogyakarta, which need to be preserved in accordance with Law No. 11 Heritage in 2010. This is phenomenology a research qualitative analysis methods. Because of the scarcity and limitations of past data related to the object of research data collection techniques applied purposive sample inductive systems, with emphasis on the acquisition of data from interviews stakeholders and manuscripts, aritkel, song. This study found three specific characters Pekapalan the three periods or time-related aspects of the palace as a function Sultanate, public functions, and the functions of culture, in the 1980s and then packed into packages. The results of this study are expected to provide an understanding of the meaning associated Pekapalan preservation of cultural heritage as a form, manner, or form various inherent of any age or generation representing it.